Diameter-height models for the Terai tree species - Khadka, A.; Subedi, T.; Ghimire, M.; Dhakal, B. P.; Parikka, H. (Banko Janakari, 2015)
Tree diameter-height relationship can be used as a key input component in forest growth and yield models, and description of stand dynamics. Various models of stem diameter and height relation were developed. Those were formulated and implemented during Terai forest inventory data calculations in the Forest Resource Assessment (FRA) Nepal Project. The field inventory was conducted from December, 2010 to March, 2011. The Concentric Circular Sample Plot was designed where the diameters at breast height of all the tallied trees and the heights of the sampled trees were measured. The data were handled with R-script in R Programme to generate non-linear mixed effects models in ‘lmfor’ package of forest biometrics functions of Mehtatalo. Different non-linear models were used to fit the diameter-height relation, which performed well in describing the relationships between the diameters and the heights of the Terai tree species depending on the sample size. The models were selected as the best fitted based on the statistical results such as standard error, Adjusted R2, RMSE and residuals. The best models for Shorea robusta and Terminalia alata were generated using Wykoff’s and Naslund’s functions, respectively. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 50-54